A riot on campus: The effects of social identity complexity on emotions and reparative attitudes after ingroup‐perpetrated violence. Issue 1 (2nd August 2017) - Costabile, Kristi A.; Austin, Adrienne B.
Abstract : When a group commits a transgression, members who identify closely with the group often engage in defensive strategies in which they are less likely to experience guilt and shame in response to the transgression than are less identified group members. Subsequently, highly identified group members are often less willing to offer reparations to the injured parties. Because appropriate emotional responses and reparations are critical to community reconciliation, the present investigation examined whether social identity complexity—the degree to which individuals perceive their multiple social identities as interrelated—reduced these defensive responses. In the aftermath of a campus riot, emotional responses and reparative attitudes of undergraduate students were assessed. Results indicated that individuals who closely identified with the university were in fact capable of experiencing guilt and shame, but only if they also had complex social identities. A path model indicated that emotional responses, in turn, predicted willingness to provide reparations to the campus community. Accordingly, social identity complexity provides a new approach to understanding responses to ingroup‐perpetrated violence.